Direct antiviral therapy for treatment of hepatitis C: A real-world study from Brazil - Oliveira Lobato, Cirley Maria de; Codes, Liana; Silva, Giovanni Faria [UNESP]; Meirelles Souza, Aecio Flavio; Moraes Coelho, Henrique Sergio; Alves Pedroso, Maria Lucia; Parise, Edison Roberto; Tojal de Barros Lima, Leila Maria Soares; Borba, Luiz Augusto; Evangelista, Andreia Silva; Fontes Rezende, Rosamar Eulira; Cheinquer, Hugo; et al. (Elsevier B.V., 2019)
Introduction and objectives: Direct antiviral agents (DAAs) including sofosbuvir (SOF), daclatasvir (DCV), simeprevir ( SIM) and ombitasvir, paritaprevir and dasabuvir were introduced 2015 in Brazil for treatment of hepatitis C virus (HCV) infection. The aims of this study were to assess effectiveness and safety of HCV treatment with DAA in real-life world in a highly admixed population from Brazil. Materials and methods: All Brazilian reference centers for HCV treatment were invited to take part in a web-based registry, prospectively conducted by the Brazilian Society of Hepatology, to assess outcomes of HCV treatment in Brazil with DAAs. Data to be collected included demographics, disease severity and comorbidities, genotype (GT), viral load, DAA regimens, treatment side effects and sustained virological response (SVR). Results: 3939 patients (60% males, mean age 58 +/- 10 years) throughout the country were evaluated. Most had advanced fibrosis or cirrhosis, GT1 and were treated with SOF/DCV or SOF/SIM. Overall SVR rates were higher than 95%. Subjects with decompensated cirrhosis, GT2 and GT3 have lower SVR rates of 85%, 90% and 91%, respectively. Cirrhosis and decompensated cirrhosis in GT1 and male sex and decompensated cirrhosis in GT3 were significantly associated with no SVR. Adverse events (AD) and serious AD occurred in 18% and 5% of those subjects, respectively, but less than 1% of patients required treatment discontinuation. Conclusion: SOF-based DAA regimens are effective and safe in the heterogeneous highly admixed Brazilian population and could remain an option for HCV treatment at least in low-income countries. (C) 2019 Fundacion Clinica Medica Sur, A.C. Published by Elsevier Espana, S.L.U.
Keywords: Chronic hepatitis C; Direct antiviral agents; Hepatic fibrosis; Cirrhosis